Comprehensive Multicenter Study of the Common Isthmus in Post–Atrial Fibrillation Ablation Multiple-Loop Atrial Tachycardia. (June 2018) - Takigawa, Masateru; Derval, Nicolas; Maury, Philippe; Martin, Ruairidh; Denis, Arnaud; Miyazaki, Shinsuke; Yamashita, Seigo; Frontera, Antonio; Vlachos, Konstantinos; Kitamura, Takeshi; Cheniti, Ghassen; Massoullieé, Greégoire; et al.
Abstract : Background: Characteristics of multiple-loop atrial tachycardia (AT) circuits have never precisely examined. Methods: In 193 consecutive post–atrial fibrillation ablation patients with AT, 44 multiple-loop ATs including 42 dual-loop AT and 2 triple-loop AT in 41 (21.2%) were diagnosed with the high-resolution mapping system and analyzed off-line. Results: In dual-loop ATs, 3 types were identified: type M, a combination of 2 anatomic macroreentrant ATs (AMATs) in 19 (43.2%); type MN, with 1 AMAT and 1 non-AMAT in 12 (27.3%); and type N with 2 non-AMATs in 11 (25.0%). The remaining 2 triple-loop ATs (4.5%) were a combination of perimitral-, roof-dependent-, and non-AMAT. At least 1 AMAT was included in 33 (75.0%), and 1 non-AMAT in 25 (56.8%). Of the ATs with at least 1 non-AMAT circuit, a pulmonary vein formed part of the circuit in 16/25 (64.0%). The length of the common isthmus was 3.6±1.4 cm in type M, 1.6±0.7 cm in type MN, and 1.1±0.7 cm in type N ( P <0.0001). The area of the common isthmus was 12.92±7.68, 2.46±1.53, and 0.90±0.81 cm 2, in Type M, MN, and N ( P <0.0001). The narrowest width of the common isthmus was 1.8±0.7 cm, 1.1±0.3 cm, and 0.7±0.3 cm in type M, MN, and N ( P <0.0001), respectively. The electrograms in the common isthmus showed longer duration and lower voltage in type N, type MN, and type M (duration: 106±25 ms, 87±27 ms, and 69±27 ms; P =0.006; and voltage: 0.06±0.02 mV, 0.22±0.21 mV, and 0.57±0.50 mV; P <0.0001), respectively. Conclusions: Multiple-loop ATs are complex, frequently including anatomic circuits. They have specific characteristics determined by the combination of AMAT and non-AMAT. Abstract : Supplemental Digital Content is available in the text.